(untitled) (Journal of the College of Basic Education, 2022)
This research aims to analyze the effect of some variables that are believed to directly affect the failure of sixth grade students in science in mathematics. The researcher used the two-response logistic regression method. A random sample of (200) male and female students was selected. By selecting ten variables: gender, intelligence level, inclinations, is the teaching method good, is the material content appropriate, the father’s educational attainment, the mother’s educational attainment, the number of study hours, does he receive private lessons, and the type of questions, which are believed to be the main cause of this problem, as The researcher used the SPSS statistical program in analyzing the research data, and the researcher concluded that three of these variables (the level of intelligence, does he receive private lessons, and the number of study hours) have a significant effect on students’ failure.